An investigation of undergraduate students' spatial thinking about groundwater. Issue 1 (1st January 2023) - White, Holly; Forbes, Cory T.
ABSTRACT: Undergraduate students may possess underdeveloped knowledge about water systems, particularly groundwater. The use of models and modeling have been employed in undergraduate classrooms to support students' learning about water. However, effective modeling requires spatial thinking skills, which undergraduate students may also need to develop. Here, undergraduate students used a computer-based groundwater model in an introductory water course and we explored students' spatial thinking about groundwater in two consecutive iterations of the course. We report findings from a descriptive study conducted in the course, through which we explored students' understanding of space, representation, and reasoning by conducting quantitative and qualitative analyses on student tasks and interviews. Findings suggest that students may struggle with certain components of spatial thinking, such as tools of representation and reasoning. Specifically, students had difficulties interpreting model representations such as contour lines, and struggled to reason about groundwater flow. However, students performed better on other aspects of spatial thinking, such as concepts of space. Overall, these results suggest students struggle with certain aspects of spatial thinking in relation to this groundwater model. These findings have implications for undergraduate teaching and learning about groundwater.